Informasi Laporan Keuangan: Studi Kasus pada Emiten BEJ - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1997)
This research extends previous researches on the impact offinancial statement announcement on the market. Specifically this research examines the following hypothesis: (1) Financial announcement has impact on the market as seen through Trading Volume Activity, Security Return Variability, and Abnormal return around announcement date, (2) December financial statements which are audited and cover longer period have more impact on the market than March financial statements. (3) Positive confirmation (March statements report profits and so do December statements) could explain the insignificant differences between SRV March statements and SRV December statements, and (4) Financial statements have impact on security prices. The research found that financial statements have impacts on the market as reflected in the significant results for TVA tests and the behavior of abnormal return during the announcements. There is a downward anticipation (cumulative abnormal return) from the market, especially for samples which failed tofulfill market expectation. SRV tests do not produce significant results as expected. This result raises a question whether TVA would be a better proxyfor information uncertainty (assitneï´y). TVA seems to be a better indicator for market reaction than does SRV. The research didn't find the difference between SRV December and SRV March, but found the difference between TVA December and TVA March. This result is interpreted as follows: Audited reports do not lessen information uncertainty (as reflected in the insignificant results for SRV), but longer period statements have more impact on the market (as reflected in the significant results for TVA). The research didn 't find evidence that positive conformation explains the insignificant results for SRV tests, butfound that the distribution of TV:4, SRV, and abnormal return for samples which failed to fulfill market expectation are different from those samples which are able to meet market expectation.